Exploiting Distinct Molecular Architectures of Ultrathin Films Made with Iron Phthalocyanine for Sensing - Volpati, D. [UNESP]; Alessio, P. [UNESP]; Zanfolim, A. A. [UNESP]; Storti, F. C. [UNESP]; Job, Aldo Eloizo [UNESP]; Ferreira, M.; Riul, A.; Oliveira, O. N.; Constantino, C. J. L. [UNESP] (Amer Chemical Soc, 2008)
The possibility of generating distinct film properties from the same material is crucial for a number of applications, which can only be achieved by controlling the molecular architecture. In this paper we demonstrate as a proof-of-principle that ultrathin films produced from iron phthalocyanine (FePc) may be used to detect trace amounts of copper ions in water, where advantage was taken of the cross sensitivity of the sensing units that displayed distinct electrical properties. The ultrathin films were fabricated with three methods, namely physical vapor deposition (PVD), Langmuir-Blodgett (LB), and electrostatic layer-by-layer (LbL) techniques, where for the latter tetrasulfonated phthalocyanine was used (FeTsPc). PVD and LB films were more homogeneous than the LbL films at both microscopic and nanoscopic scales, according to results from micro-Raman spectroscopy and atomic force microscopy (AFM), respectively. From FTIR spectroscopy data, these more homogeneous films were found to have FePc molecules oriented preferentially, tilted in relation to the substrate surface, while FeTsPc molecules were isotropically distributed in the LbL films. Impedance spectroscopy measurements with films adsorbed onto interdigitated gold electrodes indicated that the electrical response depends on the type of film-forming method and varies with incorporation of copper ions in aqueous solutions. Using principal component analysis (PCA), we were able to exploit the cross sensitivity of the sensing units and detect copper ions (Cu(2+)) down to 0.2 mg/L, not only in ultrapure water but also in distilled and tap water. This level of sensitivity is sufficient for quality control of water for human consumption, with a fast, low-cost method.